Mucinous neoplasms of the appendix - A clinicopathologic study of 21 cases with special insight into current classification & controversies. - Rajashree Pradhan,; Sajeeb Mondal,; Mrinal Sikdar,; Abhishek Bandyopadhyay, (Asian Journal of Medical Sciences, 2023)
Background : Appendiceal mucinous neoplasms are rare and heterogenous disease which often clinically present as appendicitis. There are many controversies regarding the classification of mucinous neoplasms of the appendix. Aims and Objectives: Our aim of this study was to study different types of mucinous neoplasms of appendix based on current ( WHO 2019) classification, their clinical and radiological presentations and controversies regarding their diagnosis. Materials and Methods: This was a retrospective study done in a tertiary care hospital. We studied clinical presentations of 21 cases along with the histopathological study of respective appendectomy specimens . Results: Out of 21 cases, 3 (14.28%) cases were serrated polyp, 9 cases (42.85%) were Low grade appendiceal mucinous neoplasm (LAMN), 3 cases (14.28%) were high grade appendiceal neoplasm (HAMN) and 6 (28.57%) cases were mucinous adenocarcinoma. In this study we have discussed in brief about regarding the current classification and controversies of appendiceal mucinous neoplasms. Conclusion: Mucinous neoplasms of the appendix are complex lesions with many controversies. Oversimplification in the recent classification may add to more complexity. Reintroduction of the old terminology of Mucinous Tumour of Uncertain Malignant Potential might save histopathologists from potential litigation.